HUBUNGAN KEBUTUHAN INFORMASI SEHARI-HARI DENGAN PENGGUNAAN OPENAI CHAT GPT: SURVEI PADA MAHASISWA INDONESIA - Farikasari, Nurul; Prijana, Prijana; Saeful Rohman, Asep (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2024)
This study examines the use of OpenAI Chat GPT in information retrieval by students at six leading universities in Indonesia. This study uses a quota sampling method with 600 students from Airlangga University, Brawijaya University, Diponegoro University, Gadjah Mada University, Padjadjaran University, and UIN Sunang Gunung Djati Bandung as the research sample. Pearson Product Moment correlation analysis shows that the majority of students use OpenAI Chat GPT for academic and non-academic needs with a high level of satisfaction. There is a significant relationship between students' daily information needs and the use of OpenAI Chat GPT. Valuable and useful information is correlated with more efficient and accurate information retrieval. This study supports the new media theory which states that digital technology changes the way individuals interact with information, enabling more personal and interactive experiences. This study provides theoretical contributions to the literature on the use of AI technology in information retrieval and practical recommendations for further research development.